Peran Guru Dalam Proses Pembelajaran di Kurikulum Merdeka Kelas IV SDN Kwadungan Lor - Sari, Riza Solehah Intan; Permata, Santy Dinar; Mashuri, Anwas (Civiliza Publishing, Indonesia., 2023)
This research aims to determine the role of teachers in the learning process in the fourth grade independent curriculum at SDN Kwadungan Lor. The independent curriculum has been implemented at Kwadungan Lor Elementary School. The role of teachers in the independent curriculum learning process has been carried out well. The method used in this research is a qualitative method. The data collection techniques used in this research include observation, interviews and documentation studies. Data validity techniques are carried out with trust (credibility) and certainty (confirmability). The data analysis techniques used in this research include data collection, data validation, data presentation, and drawing conclusions. The research results show that students receive learning with an independent curriculum, schools and teachers are very supportive of the independent curriculum, and teachers are more flexible to be as creative in teaching as possible, and know more about students' requests, talents, needs and abilities.